Chemical composition, in vitro gas production, and nutrient degradability of carob leaves as a sustainable feed for ruminants in Tunisia and Palestine - Ghzayel, Soha; Ammar, Hajer; Zoabi, Halimeh; Abou Aziz, Bassem; Kholif, Ahmed E.; Adegbeye, Moyòsore J.; Ben Abdallah, Rym; de Haro-Martí, Mario; Lopez, Secundino; Chahine, Mireille (Frontiers in Veterinary Science, 2025)
IntroductionCarob leaves may be a potential roughage source for ruminants in arid areas. The nutritive value of this feedstuff may be considerably enhanced by the application of solid-phase chemical treatments. This study aimed to evaluate the nutritive value of carob leaves collected from Tunisia and Palestine untreated or treated with urea or sodium hydroxide (NaOH), or supplemented with polyethylene glycol (PEG) on chemical composition and in vitro ruminal fermentation.MethodsCarob leaf samples were collected from either Palestine or Tunisia, and were used either untreated (control) or treated with urea, NaOH at 4% or PEG at 100 mg/g (dry matter (DM) basis), and analyzed for chemical composition. Carob leaves were incubated in vitro in diluted rumen fluid fermentation for 48 h, measuring fermentation gasses [methane (CH4), and carbon dioxide (CO2)], DM degradability and fermentation kinetics.Results and discussionResults showed a significant country × treatment interaction for most measured parameters, indicating that treatment effects are constrained by the origin of the leaves. Palestine untreated carob leaves had higher (p < 0.001) crude fat, crude protein (CP) and neutral detergent fiber (NDF), but less nonstructural carbohydrate (NSC), acid detergent fiber (ADF) and acid detergent lignin than Tunisia leaves. Tunisia carob leaves had higher concentration (p < 0.01) of flavonoids and tannins than leaves from Palestine. Of the three treatments tested, the addition of PEG increased (p < 0.01) the gas production during the incubation in diluted rumen fluid of carob leaves and this effect was greater with leaves from Palestine than with those from Tunisia. The other treatments had less noticeable effects, which were different when applied to the leaves from one or another country, given the significance of the interaction country × treatment detected for most of the variables studied. PEG, NaOH and urea treatments of carob leaves can be applied to enhance the ruminal fermentation and energy value of this feedstuff. However, the effects of these treatments are highly dependent on the parent material, and seem to be more effective when applied to a low digestible material.